Activity of N-Hexane, Ethyl Acetate and Methanol Extracts from Passiflora foetida Leaves as α-Glucosidase Enzyme Inhibitor - Nita Triadisti; Irfan Zamzani (JCPS (Journal of Current Pharmaceutical Sciences), 2021)
Diabetes mellitus is a major health problem characterized by an increase in postprandial blood glucose levels, where α-glucosidase enzyme inhibitors are an effective therapeutic option. The limited choice of α-glucosidase enzyme inhibitors has triggered a study to obtain new α-glucosidase inhibitor candidates. Kelubut (Passiflora foetida) has been used for generations in the treatment of diabetes in Kalimantan, usually the roots and leaves are part of the plant used in the treatment of diabetes. Scientific data regarding α-glucosidase inhibition have not been reported. The extraction was carried out using the multilevel maceration method, while the α-glucosidase inhibition test was carried out by the spectrophotometric method using a microplate reader. The assay results showed that all extracts had inhibitory activity against α-glucosidase, and the best activity was the methanol extract of Passiflora foetida leaves with IC50 580.04 µg / mL